CHALLENGES IN THE CIRCULAR ECONOMY OF BULGARIA (Innovation in Woodworking Industry and Engineering design, 2026)
The transition towards a circular economy presents a transformative challenge with the potential to yield extensive economic, environmental, and societal benefits. In Bulgaria, the shift from a traditional linear economy to a circular one is fraught with a unique set of challenges, which this paper meticulously examines. Through qualitative and quantitative analysis, the paper identifies the primary barriers impeding the adoption of circular economy practices, including inadequate regulatory frameworks, insufficient technological infrastructure, and the entrenched habits of consumption and production that resist change. It explores the role of government policy, business innovation, and consumer engagement in fostering a conducive environment for the circular economy. The paper also discusses the potential for economic growth and sustainability that a circular economy can offer within the Bulgarian context, suggesting strategic approaches to leverage indigenous resources, and encouraging collaboration between sectors. Through this exploration, the paper provides valuable insights and proposes actionable recommendations that aim to guide policymakers, business leaders, and civil society in overcoming these challenges and achieving a sustainable circular transition in Bulgaria.